Saul Januarie: Biography of a wagon-maker and blacksmith from Worcester, Western Cape, South Africa - Esau, Cecyl (University of the Western Cape, 2013)
Magister Artium - MA === Saul Januarie was born in Worcester in 1903. He spent his childhood years in the town of Touwsriver and then returned to Worcester as an adult where he married and spent the remainder of his life. He became well-known as a blacksmith from Worcester from the 1930's omwards. His skills were sought after in the town as well as on the farms in the surrounding area. Januarie was also renowned as a leader of the Independent Order of True Templars (IOTT). This study was an important starting-point to contribute to the exploration of a more inclusive social history of Worcester. The biography of Saul Januarie that has been constructed lends itself eminently to complement and enlarge the present exhibitions on wagon-making and the work of blacksmiths. === South Africa